Causes of lipodystrophy - Korabiusz, Katarzyna; Wawryków, Agata (Journal of Education, Health and Sport, 2018)
Abstract Lipodystrophy is one of the most common and the most undesirable female dermatological conditions. Both slim and overweight people can struggle with it. It is possible to fight cellulite with various physiotherapeutic techniques and methods.Research goal: Goal of this dissertation is a review of literature about causes of lipodystrophyConclusion: Lipodystrophy is a condition with a multifactorial etiology. One should be aware that only multidirectional treatment can bring satisfactory results.